Response and Disease Dynamics in Untreated Metastatic Colorectal Cancer With Bevacizumab-Based Sequential vs. Combination Chemotherapy—Analysis of the Phase 3 XELAVIRI Trial - Kurreck, Annika; Heinemann, Volker; Fischer von Weikersthal, Ludwig; Decker, Thomas; Kaiser, Florian; Uhlig, Jens; Schenk, Michael; Freiberg-Richter, Jens; Peuser, Bettina; Denzlinger, Claudio; Graeven, Ullrich; Heinrich, Kathrin; et al. (Frontiers in Oncology, 2022)
Introduction Early tumor shrinkage (ETS), depth of response (DpR), and time to DpR represent exploratory endpoints that may serve as early efficacy parameters and predictors of long-term outcome in metastatic colorectal cancer (mCRC). We analyzed these endpoints in mCRC patients treated with first-line bevacizumab-based sequential (initial fluoropyrimidines) versus combination (initial fluoropyrimidines plus irinotecan) chemotherapy within the phase 3 XELAVIRI trial. Methods DpR (change from baseline to smallest tumor diameter), ETS (≥20% reduction in tumor diameter at first reassessment), and time to DpR (study randomization to DpR image) were analyzed. We evaluated progression-free survival and overall survival with ETS as stratification parameter according to treatment arm, molecular subgroup, and sex. Results In 370 patients analyzed, a higher rate of ETS (60.9% vs. 43.5%; p = 0.001) and significantly greater DpR (-40.0% vs. -24.7%; p < 0.001) were observed in the initial combination therapy arm. The improvement was pronounced in RAS/BRAF wild-type tumors. ETS correlated with improved survival irrespective of treatment arm (PFS: p < 0.001; OS: p = 0.012) and molecular subgroup (PFS: p < 0.001; OS: p < 0.001). Male patients in contrast to female patients with ETS had survival benefit (PFS: p < 0.001, HR 0.532; OS: p < 0.001, HR 0.574 vs. PFS: p = 0.107; OS: p = 0.965). Conclusions Initial irinotecan-based combination therapy with bevacizumab improved ETS and DpR in mCRC patients with a particularly high irinotecan sensitivity of RAS/BRAF wild-type tumors. ETS seems to be a suitable prognostic marker for fluoropyrimidine- and bevacizumab-based combinations in mCRC. This finding was rather driven by male patients, potentially indicating that ETS might be less predictive of long-term outcome in an elderly, female population.